Mobile Data Loss: Threats and Countermeasures. Issue 6 (June 2016) - Unknown
Abstract : While the focus of many organisations has been on protecting their servers and network infrastructure, a rapid evolution has been underway at the endpoints of their networks. The changes wrought there may have rendered what little attention they have given to the endpoint largely null and void.